Pregnancy Complications and Fetal Outcomes in Obese Pregnant Women in a Tertiary Care Center in Eastern Nepal - Neupane, Bhanubhakta; Karki, Gyanendra Man Singh; Yadav, Siddhartha Kumar; Pandey, Shuvechha (Journal of Nobel Medical College, 2025)
Background: Weight gain in pregnancy is normal, but obesity prior to pregnancy may be associated with increased risk of pregnancy and neonatal complications. Materials and Methods: This comparativecross sectional study was conducted in Birat Medical College Teaching Hospital from 2024 August 15 to 2025 May 15, over the period of 9 months. Three hundreds and thirty participants were enrolled in the study, 165 women with Body Mass Index (BMI) 30 as study group and 165 women with normal BMI as reference group. Obstetric and neonatal outcomes were compared between the two groups using student’s t test and Chi-square test. Results: The mean BMI was 32.5±2.56 kg/m2 in study group and 23.20±1.5 kg/m2 in reference or normal weight group. The incidence of Gestational diabetes mellitus (GDM) was 16.97% vs 6.66%(RR2.54,95% CI1.62-3.20, p=0.02), hypertensive disease in pregnancy (HDP) was 21.21% vs 8.48%, (RR 2.5, 95% CI 1.84-2.60, p=0.01) and caesarean section rate was 56.96% vs 30.30% (RR 1.88, 95% CI 1.52-2.70) in study group and reference group respectively. Neonatal admission rate was 23.03% in obese group and 16.36% in normal weight group. Incidence of neonatal death was similar in both groups. Conclusion: Obese pregnant women have higher risk of pregnancy and neonatal complications when compared with normal BMI women.